Analysis of weighted network centrality for cold chain commodities in international air cargo under the COVID-19 pandemic - Youngwoong Park; Seung-Bum Ahn; Jae Chul Sohn (Asian Journal of Shipping and Logistics (AJSL), 2023)
Air Cargo plays a key role under the global supply chain crisis brought about by COVID-19 pandemic. This study aims to analyze empirically the transport patterns and correlations of key commodities of cold chain in air cargo. We analyzed air cargo O-D data by weight for key commodities including pharmaceutical and coolchain products for top 100 airports in the last 10 years. We analyzed weighted centralities for key cold chain commodities traffic using social network analysis methodology. Whereas previous studies focused on unweighted centrality metrics, this study covered weighted centrality metrics, which represent more accurate empirical situation. The international air cargo networks for cold chain are significantly improved after COVID-19. Comparative analysis of cold chain traffic trends for top 10 international air cargo airports was also performed. The role of top 10 airports in the performance of air cargo transportation was found to be more important, especially in COVID-19 period.
Keywords: 650; Air cargo; Cold chain; Social network analysis; Weighted centrality; Weighted network